Kierkegaard, MacIntyre, Williams, and the Internal Point of View - Compaijen, Rob (Springer International Publishing, 2018)
This book takes the debate about the (ir)rationality of the transition to ethical life in Kierkegaard's thought in a significantly new direction. Connecting the field of Kierkegaard studies with the meta-ethical debate about practical reasons, and engaging with Alasdair MacIntyre's and Bernard Williams' thought, it explores the rationality of the choices for ethical life and Christian existence. Defending a so-called 'internalist' understanding of practical reasons, Compaijen argues that previous attempts to defend Kierkegaard against MacIntyre's charge of irrationality have failed. He provides a thorough analysis of such fundamental topics as becoming oneself, the ideal objectivity in ethics and religion, the importance of the imagination, the power and limits of philosophical argument, and the relation between grace and nature. This book will be of great interest to Kierkegaard scholars (both academics and graduate students) in philosophy and theology, and, more generally, to anyone fascinated by the rationality of the transition to ethical life and the choice to accept Christianity.